Analysis of The Factors of Competitive Advantage of Women SME Actor: Empirical Study From Limo Sub-District, Depok City, Indonesia - Nobelson, N.; Yuliniar, Y. (Manunggal Halim Jaya, 2025)
The development of the SME sector plays a vital role in the Indonesian economy, contributing significantly to gross domestic product, employment, and exports. Despite the complex challenges, attention to women's SMEs is increasing in the Limo District, Depok City. This quantitative research uses the factor analysis method to analyze the competitive advantage factors of women SME actors with a sample of 100 persons. This study identifies and analyzes the application of competitive advantage factors that support the performance of women SMEs. The results show that women SMEs can adapt and innovate despite capital and knowledge limitations. The implications of this research guide for the government and related institutions to formulate strategies to improve the performance and contribution of women SMEs in sustainable economic development in the region.